Crowdfunding: The Two Sided Financing Alternative - Nordin, Norhafiza; Md. Sum, Rabihah (Journal of Technology Management and Business, 2020)
This paper examines crowdfunding, an internet-based source of financing and investment tool, which is gaining popularity due to its simpler and faster process compared to the traditional financing and investment tools. Although it has a handful of benefits and potentials, the threats associated with it should not be ignored. Information asymmetry is one of the problems identified. High information asymmetry may exist when the fund seekers intentionally do not fully disclose some information in order to protect their own interest. Consequently, the limited information disclosure could result in adverse wealth effect to the contributors or investors. This paper contributes to the extant literature by providing thematic discussions about the crowdfunding’s practices, threats and opportunities based on the information gathered from a desktop research. The findings would be able to provide insights to the fund seekers looking for funding and to the potential investors looking for an alternative investment product.